Invisible as air : a novel - Fishman, Zoe (William Morrow, An Imprint of HarperCollins Publishers, 2019)
Sylvie Snow knows the pressures of expectations: a woman is supposed to work hard, but never be tired; age gracefully, but always be beautiful; fix the family problems, but always be carefree. Sylvie does the grocery shopping, the laundry, the scheduling, the schlepping and the PTA-ing, while planning her son's Bar Mitzvah and cheerfully tending her husband, Paul, who's been lying on the sofa with a broken ankle. She's also secretly addicted to the Oxycontin intended for her husband. For three years, Sylvie has repressed her grief about the heartbreaking stillbirth of her newborn daughter, Delilah. On the morning of the anniversary of her death, when she just can't face doing one...more...thing: she takes one--just one--of her husband's discarded pain pills. And suddenly she feels patient, kinder, and miraculously relaxed. She tells herself that the pills are temporary, just a gift, and that when the supply runs out she'll go back to her regularly scheduled programming. But days turn into weeks, and Sylvie slips slowly into a nightmare. At first, Paul and Teddy are completely unaware, but this changes quickly as her desperate choices reveal her desperate state. As the Bar Mitzvah nears, all three of them must face the void within themselves, both alone and together.